2021
DOI: 10.3390/su13116266
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sustainable Decommissioning of Offshore Platforms in the Oil and Gas Industry: A PESTLE Analysis

Abstract: The growing complexity of environmental challenges has progressively led to the emergence of Sustainable Business Models (SBMs) able to embed economic, environmental, and social flows in a unified value network. All sectors are demanding innovative and sustainable solutions, including the oil and gas industry, which aims to address the issues about the decommissioning of offshore platforms. However, although the relevant literature highlighted the potentialities related to a multi-reuse of these structures, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 82 publications
(116 reference statements)
0
24
0
Order By: Relevance
“…IMTA is a production technology capable of reducing pollution while increasing productivity and profits by converting waste streams into new products, allowing for production improvement, supply system diversification, and cost reduction." Furthermore, the SCBMC provides a holistic framework by integrating ecosystem logic, i.e., the "trends and drivers" of the macro-environment with a PESTLE analysis (Capobianco et al, 2021) and stakeholder participation and interaction dynamics. On the other hand, at the lower part of the SCBMC business level are the sustainability impacts.…”
Section: Discussionmentioning
confidence: 99%
“…IMTA is a production technology capable of reducing pollution while increasing productivity and profits by converting waste streams into new products, allowing for production improvement, supply system diversification, and cost reduction." Furthermore, the SCBMC provides a holistic framework by integrating ecosystem logic, i.e., the "trends and drivers" of the macro-environment with a PESTLE analysis (Capobianco et al, 2021) and stakeholder participation and interaction dynamics. On the other hand, at the lower part of the SCBMC business level are the sustainability impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Is there a standard transdisciplinary decision-making assessment process from other industries that can be adapted/applied to decommissioning decisions for offshore structures; and if not, what is needed to develop one? Many peer-reviewed studies have evaluated the suitability of existing decision-making assessment processes for the decommissioning of offshore structures (such as, Comparative Assessments, Multi-criteria Decision Assessments, Life Cycle Assessments, amongst others, e.g., Fowler et al, 2014;Martins et al, 2020;Capobianco et al, 2021;Colaleo et al, 2022a;Lemasson et al, 2022;Vidal et al, 2022). A common finding of these studies is that the multitude of factors involved with offshore decommissioning have not, to date, been considered comprehensively.…”
Section: Transdisciplinary Decommissioning Assessment Standardsmentioning
confidence: 99%
“…Table A1 in the Appendix indicates the main SDG dimensions and the opportunities to integrate SDGs into decommissioning programs. Recent studies have demonstrated a sustainable decommissioning approach in the energy industry (Topham et al 2017;Invernizzi et al, 2020;Zawawi et al, 2012;Capobianco et al, 2021). To integrate sustainability in decommissioning programs, social, environmental, and economic dimensions must be considered, as well as the ways in which these interconnect.…”
Section: Integrating Sustainability and Circularity In Decommissionin...mentioning
confidence: 99%
“…Moreover, by unveiling the stakeholders' perspectives, the study shows that considerable attention should be placed on them in decisions about decommissioning and reuse to ensure that, as decommissioning, reuse, planning, and implementation proceed, stakeholders' needs and concerns are properly addressed, thus improving the probability of success. In the end-of-life management of Italian offshore platforms, the adoption of a sustainable perspective and the consideration of the opportunities derived from the application of CE principles can preserve the environment and create new economic and social value (Loia et al, 2021 a,b;Capobianco et al, 2021). In the complex context of platform end-of-life activities management, a circularity approach aims to use resources more efficiently, keep resources in use for as long as possible, and minimise waste.…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%